Achievement motivation and small business success in Transkei - Mahadea, D (Development southern Africa (Sandton, South Africa), 1994)
The success of small firms is crucial for the creation and expansion of employment opportunities. Success in business often relies on entrepreneurial skills and attributes. This article examines the effect of one of these attributes, need achievement (n-Ach), on entrepreneurial success as measured by asset, sales and labour growth. N-Ach was found to be a significant predictor of success for indigenous entrepreneurs in Transkei Subjects with high and above-average n-Ach level tended to engage in more sophisticated business ventures than their counterparts low on n-Ach. Male entrepreneurs were found to have a higher mean score on n-Ach than their female counterparts. A one-unit enhancement in n-Ach level of the entrepreneur could induce a more than proportionate rise in the labour growth rate of the small entrepreneurial firm.